نواندنی پێكهاتەی ڕستە لە هێڵكاریی درەختیدا - حسەین, ئازاد ئەحمەد (Sulaimani Journal for Humanities, 2022)
This research, entitled (Representing the structure of the sentence in the tree diagram), explains the relationship that exists between the components of the sentence and the result of the structure.The tree diagram is a complement to other analyzes and studies of the sentence, and it shows grammatical and precise information, which changes according to the types of sentence.That is, each sentence has its own scheme that distinguishes it from another sentence.On the other hand, the components of the sentence may have more than one level, which are shown in the tree diagram.Generally, structural relationships are divided into two groups: (horizontal relationships) and (vertical relationships). The tree diagrams used in this research are based on the theorem (x-bar), and this theory has its own importance in the sentence structure.